1998
DOI: 10.1046/j.1432-1327.1998.2530212.x
|View full text |Cite
|
Sign up to set email alerts
|

Bdellastasin, a serine protease inhibitor of the antistasin family from the medical leech (Hirudo medicinalis)

Abstract: We have reported earlier the isolation and amino acid composition of bdellin A from medical leech, and characterised it as an inhibitor of trypsin, plasmin and acrosin [Fritz, H., Gebhardt, M., Meister, R. & Fink, E. (1971) in Proceedings of the international research conference on proteinase inhibitors (Fritz, H. & Tschesche, H., eds) pp. 271Ϫ280, Walter de Gruyter, Berlin]. In the present study, one of several chromatographic forms of this inhibitor was isolated from a semi-pure preparation. Elucidation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 23 publications
0
34
0
1
Order By: Relevance
“…Using the culture conditions described by Moser et al (19), ϳ10 mg/L of recombinant elafin peptides were consistently recovered in the yeast culture media. This is lower than the 29 mg/L of bdellastasin, a 6-kDa serine protease inhibitor, obtained by Moser et al from an analogous fusion protein also cloned in a pVT plasmid (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the culture conditions described by Moser et al (19), ϳ10 mg/L of recombinant elafin peptides were consistently recovered in the yeast culture media. This is lower than the 29 mg/L of bdellastasin, a 6-kDa serine protease inhibitor, obtained by Moser et al from an analogous fusion protein also cloned in a pVT plasmid (19).…”
Section: Resultsmentioning
confidence: 99%
“…Pilot experiments for the detection of recombinant elafin molecules were performed with small volumes of yeast culture grown for 3 days in selective medium. For the purification of large amounts of recombinant elafin peptides, we adopted the growth conditions developed by Moser et al for the production of bdellastasin (19). Briefly, a 3-day preculture in selective medium (100 mL) is diluted to 1 L with a culture medium composed of 0.67% Bacto yeast extract, 0.67% NaH 2 PO 4 , and 2% D-glucose.…”
Section: Strains Oligonucleotides and Dna Manipulationsmentioning
confidence: 99%
“…Similarly to the other antistasin family inhibitors, eisenstasin I and II feature 3 and 4 internal repeats, respectively, of a 24-29 amino acid sequence. The internal repeat, exhibiting a highly conserved pattern of either the 5-cysteine/2-glycine as in most leech antistasins (Moser et al 1998) or the 6-cysteine/2-glycine as in hydra antistasin (Holstein et al 1992), is a striking feature of the antistasin family. Although the repeats are not identical with regard to length or number, the internal repeats in eisenstasin I and II show a conserved pattern of 6-cysteine/2-glycine, at identical positions between the third and fourth cysteine residues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Amino acid sequence analysis revealed that antistasin is a cysteinerich peptide, featuring internal repeats which contain the conserved 6 cysteine and 2 glycine residues. This suggests that the antistasin gene has evolved via gene duplication (Moser et al 1998). The number of internal repeats depends, however, on the species.…”
Section: Introductionmentioning
confidence: 99%
“…therefore, it was renamed bdellastasin to avoid confusion with Bdellin B, which is another trypsin-plasmin inhibitor from the medical leech, but of the Kazal type. Bdelastasin does not manifest inhibitor activity towards Factor Ха, chimotripsin, thrombin, tissue or plasma kalikrein, but its Ki values for inhibition of bovine trypsin are of nanomolar range (64). Steinmetzer et al (1999) reported on the highly potent and specific synthetic thrombin inhibitors derived from the natural polypeptide hirudin which they named hirulogs.…”
Section: Natural Inhibitors Of Serine Proteasesmentioning
confidence: 99%